Assessment of Nurses’ Knowledge and Management of Diabetic Foot and its Correlation with Hba1c Levels in Al-Diwaniyah Hospitals - Al-foa'adi, Ala'a Hasan Jasim; Mohammad, Yahia Falih (Journal of Science in Medicine and Life, 2026)
One of the main consequences of diabetes mellitus is diabetic foot, which can result in infection, ulceration, or even amputation. Nurses are essential to management, early detection, and prevention. Poor patient outcomes, however, might be caused by gaps in practice and knowledge. HbA1c is a crucial biomarker that indicates the risk of complications and glycemic management. Objective: to evaluate nurses' diabetic foot knowledge and treatment methods and ascertain how they relate to patients' HbA1c levels at Al-Diwaniyah hospitals. Methods: A cross-sectional descriptive-correlational study was carried out among nurses in particular hospitals in Al-Diwaniyah. Knowledge and the Management/Practice Checklist were evaluated using a structured questionnaire, and real practices were verified using an observation checklist. Patients' HbA1c readings (from records within three months) were connected to the care provided by the corresponding nurses. Descriptive statistics, regression testing, and correlation were used to examine the data. Results: One hundred nurses who worked in the hospitals of Al-Diwaniyah took part in the study. The majority of participants were male (59%) and held a Bachelor of Science in Nursing (54%). Regarding diabetic foot care, over half of the nurses demonstrated strong understanding (53%) and good management techniques (55%). However, a significant portion lacked sufficient practice (39%) and expertise (35%). Of the patients, 39% had poor control and 57% had moderate HbA1c. Nurses' expertise (r = −0.688, p < 0.001) and management techniques (r = −0.709, p < 0.001) were found to be highly adversely linked with HbA1c levels. Conclusions: Patient outcomes, especially glycemic control, can be improved by strengthening evidence-based practices and expanding nurses' expertise. Ongoing supervision and training are advised.